2022
DOI: 10.7717/peerj.13430
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofHelicobacter pyloriin Australia: a scoping review

Abstract: Background Helicobacter pylori (H. pylori), a bacterium implicated in the development of peptic ulcer and gastric cancer, is estimated to infect around half the world’s population. Its prevalence in Australia is unclear. This scoping review aimed to evaluate all Australian literature providing estimates of the prevalence of H. pylori. Methods Australian studies examining H. pylori prevalence from 1982 onwards were eligible for inclusion. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…This study found that approximately 15% of all NITs for H. pylori were positive. This matched the reported prevalence of H. pylori in Australia which has been estimated to range between 15.1% and 38.0% [34]. When looking at NIT methodologies, this study suggested that clinicians in the Illawarra Shoalhaven regions prefer UBT as the primary noninvasive H. pylori detection method.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study found that approximately 15% of all NITs for H. pylori were positive. This matched the reported prevalence of H. pylori in Australia which has been estimated to range between 15.1% and 38.0% [34]. When looking at NIT methodologies, this study suggested that clinicians in the Illawarra Shoalhaven regions prefer UBT as the primary noninvasive H. pylori detection method.…”
Section: Discussionsupporting
confidence: 79%
“…In Australia, prevalence has been estimated to range between 15.1% and 38.0% with increasing prevalence recognised amongst subgroups such as indigenous or elderly populations [34]. For this study, the prevalence in each population area was calculated under the assumption that the positive H. pylori result was representative of the total area population.…”
Section: Discussionmentioning
confidence: 99%
“…Congedi et al published a scoping review that reported a decreased tendency of H. pylori infection among Australian citizens. Nevertheless, the scoping review could not confirm the infectious potential of H. pylori among susceptible clusters [22]. Another systematic review conducted by Peleteiro et al reported that the highest and lowest rates of H pylori infection were found in Mexico (90%) and Finland (13.1%), respectively [23].…”
Section: Introductionmentioning
confidence: 98%